Trueness and precision of the reproduction of dental casts by the conventional, milling and 3D printing techniques - Viegas, Diogo Cabecinha; Lima Hermínio, Joana; Fernandes, João; Arrobas, Fernando; Roque, João Carlos; Mourão, João Tiago; Saavedra, Guilherme (Brazilian Dental Science, 2021)
Objective: To compare the reproduction trueness and precision of dental casts made by the conventional, milling and 3D printing techniques. Material and Methods: From an upper right side half-arch reference model (RM), 72 models were obtained and divided into three groups: conventional (CM), milled (MM) and printed (PM). All models were scanned and converted into standard tessellation language (.STL) files. The files were superimposed using 3D analysis software, and statistical analysis was performed using the root mean square (RMS) values obtained. The Shapiro-Wilk test was used to assess normality, and the Kruskal-Wallis test was used to compare groups (p < 0.05). The Mann-Whitney U test was used for multiple comparisons among groups (p < 0.017). Results: There were significant differences in trueness (p = 0.000; p <0.001) and precision (p = 0.000; p < 0.001) among the three dental cast groups. Regarding trueness, CM presented better results, followed by MM and PM. Regarding precision, MM showed better results, followed by PM and CM, which did not show significant differences. Conclusions: For dental cast reproduction the conventional technique has the best trueness and the milling technique has the best precision. KEYWORDS Trueness; Precision; Milling; 3D printing; Dental cast.